The Gifts of Athena: Historical Origins of the Knowledge Economy - Mokyr, Joel (Journal of Economic Sociology, 2012)
In The Gifts of Athena, Joel Mokyr constructs an original framework to analyze scientific and technical progress appeared in the modern West in the past two centuries. The progress was driven not just by the appearance of new technological ideas but also by the improved access to these ideas in society at large. Through a wealth of historical evidence set, he shows that changes in the intellectual and social environment and the institutional background in which knowledge was generated and disseminated brought about the Industrial Revolution, followed by sustained economic growth and continuing technological change.The journal publishes chapter 7 of The Gifts of Athena — «Institutions, Knowledge, and Economic Growth», in which Joel Mokyr discusses the role of institutional factors and useful knowledge for the economic growth of the Western economies.